The Effect of Mother's Hypertension and Weight and Parent's Smoking Habit on Low Birth Weight Deliveries in Hospital, Kuala Lumpur, Malaysia - Latiffah A Latiff; Parichehr Hanachi (Tehran University of Medical Sciences, 2010)
Objective: Maternal factors such as age, health, diet, and environment are significantly associated with low birth weight. The objectives of this study were to determine the incidence, distribution and major risk factors of low birth weight in Hospital Kuala Lumpur. Materials and methods: A hospital based case-control study was done in Obstetric Ward of Maternity Hospital in Hospital Kuala Lumpur. Data was obtained using questionnaire and Performa. Out of 1021 deliveries, 330 were selected randomly as respondents that comprises of 110 cases and 220 controls. The outcome measure was low birth weight (<2500 grams). Results: The incidence of low birth weight was 10.8%. Among races, the highest occurrence of low birth weight was in Malay, while the highest age group was between 21 years old to 34 years old with majority of the respondent were married. Among the maternal socio-demographic factors, maternal height of less than 150 cm has a significant relationship with low birth weight. In addition, maternal weight of 45 kg and less and maternal weight gain during pregnancy of less than 10 kg were also found to be risk factors. However, none of the socio-demographic factors were significantly associated with low birth weight deliveries. Similarly, signs of premature delivery, maternal vaginal bleeding and fetal growth retardation (IUGR) had a significant association. Conclusion: The mothers that have experienced any of the risks that were identified should be monitored and effective prevention should be taken to decrease the chances of low birth weight but not forgetting to promote a health lifestyle to the mother and father as well.